An ultrawideband (UWB) slotline antenna under multiple-mode resonance - Huang, X. D. (2013)
A novel ultrawideband (UWB) antenna based on a multiple-mode slotline radiator is proposed and developed. This slotline radiator/resonator is formed on the ground plane of a microstrip line and it is asymmetrically fed in right angle by a shorted strip conductor. As the feeding position and port impedance are properly selected, an operating band (VSWR <; 2.0) of 3.6 to 10.5 GHz with four reflection zeros is realized. A practical 50-Ω microstrip-fed slotline resonator antenna is then constructed with a tapered line transformer. After its radiation performance is optimally designed, a prototype UWB antenna is fabricated and measured. The measured impedance bandwidth has successfully achieved a fractional bandwidth of 97.9% (VSWR <; 2.3) as predicted in theory, over which the antenna peak gain varies from 0.5 to 4.5 dBi.